A dual change model of life satisfaction and functioning for individuals with schizophrenia - Edmondson, Melissa (2012)
Despite the notion that increases in functioning should be associated with increases in life satisfaction in schizophrenia, research has often found no association between the two. Dual change models of global and domain-specific life satisfaction and functioning were examined in 145 individuals with schizophrenia receiving community-based services over 12 months. Functioning and satisfaction were measured using the Role Functioning Scale and Satisfaction with Life Scale. Data were analyzed using latent growth curve modeling. Improvement in global life satisfaction was associated with improvement in overall functioning over time. Satisfaction with living situation also improved as independent functioning improved. Work satisfaction did not improve as work functioning improved. Although social functioning improved, satisfaction with social relationships did not. The link between overall functioning and global life satisfaction provides support for a recovery-based orientation to community based psychosocial rehabilitation services. When examining sub-domains, the link between outcomes and subjective experience suggests a more complex picture than previously found. These findings are crucial to interventions and programs aimed at improving functioning and the subjective experiences of consumers recovering from mental illness. Interventions that show improvements in functional outcomes can assume that they will show concurrent improvements in global life satisfaction as well and in satisfaction with independent living. Interventions geared toward improving social functioning will need to consider the complexity of social relationships and how they affect satisfaction associated with personal relationships. Interventions geared towards improving work functioning will need to consider how the quality and level of work affect satisfaction with employment.